Pengaruh Keteladanan dan Kewibawaan Guru terhadap Sikap Tawadhu Siswa di MTs dan MA Sunan Drajat Geger - Bojonegoro Tahun Pelajaran 2015 - Qomaro, Galuh Widitya (Didaktika Religia, 2016)
This study is intended to investigate the influence of modeling and authority of teachers (partially and simultaneously) to the attitude of students at MTs and MA Sunan Drajat Geger Bojonegoro, academic year 2015. The data collections used were questionnaire and documentation. The number of subjects were 40 respondents drawn using random sampling techniques. Data obtained from the questionnaire were analyzed using Correlation Analysis and Multiple Regression. The finding reveals that the most influential factor towards students’ attitudes is modeling with regression coefficient of 0.972 (97.2%). Authority has positive effect towards students’ attitude though not significant with a regression coefficient of 0.02 (2%). In testing the hypothesis using F test, the two variables modeling (X1) and authority (X2) simultaneously affect the students’ attitude. This can be seen from the value of F which is greater than the F table.